Family carers' knowledge and practices in dementia care for hospitalized older adults: a multi-center cross-sectional study in Thailand - Anantapong, Kanthee; Wongpakaran, Nahathai; Setthawatcharawanich, Suwanna; Aphisitphinyo, Sirinapa; Sirimaharaj, Nopdanai; Rattanabannakit, Chatchawan; Paholpak, Pongsatorn; Jiraphan, Aimorn; Wiwattanaworaset, Pakawat; Aunjitsakul, Warut; Buathong, Napakkawat; Paholpak, Pattharee; et al. (Frontiers in Medicine, 2025)
BackgroundDementia-friendly hospital care is a growing priority in Thailand as the population ages, but the knowledge and experiences of family carers within well-resourced university hospitals remain underexplored—particularly regarding how care processes and cultural context affect outcomes.MethodsThis multi-center cross-sectional study surveyed 136 family carers of older adults with dementia, recruited from outpatient clinics at four major university hospitals across Thailand. Data were collected via structured interviews assessing carer demographics, dementia knowledge using the DKAS-Thai scale, and carer experiences of hospital dementia care using the Implementation and Sufficiency of Dementia-Friendly Practices (ISDP) tool. Group comparisons and associations were explored using descriptive statistics and ANOVA.ResultsCarers' knowledge about dementia was moderate overall, with higher scores among those with greater education and previous dementia exposure. Nevertheless, persistent gaps were noted, especially regarding the reversibility of dementia and behavioral management. While over 80% of carers reported adequate involvement in daily care and decision-making, the implementation of hospital dementia-friendly practices was inconsistent. Nearly half of respondents reported a lack of systematic dementia identification, limited individualized care planning, and insufficient discharge communication. Site-level differences and cultural influences, including filial obligation and low expectation of formal support, contributed to pronounced variability in carers' experiences. No significant linear association between DKAS-Thai and ISDP scores was observed, suggesting that knowledge alone may not translate into improved care experiences in complex, variable hospital settings. Carers highlighted insufficient communication, limited family participation in discharge planning, and gaps in advance care planning and palliative access, despite specialist hospital resources.ConclusionsSignificant variability in dementia care implementation and knowledge persists across Thailand's university hospitals, highlighting the interplay of institutional practices and cultural factors. System-level interventions—such as standardized dementia screening, routine family involvement in multidisciplinary planning, and culturally responsive education for carers and staff—are recommended to bridge these gaps. These findings underscore the need for action not only in university hospitals but also in developing broader national dementia care strategies adapted to Thailand's social context.